Analisis Pembangunan Sumber Daya Manusia dan Pertumbuhan Ekonomi Provinsi-provinsi di Indonesia - Saepudin, Tete (Jurnal Trikonomika, 2011)
The objective of the present study is to analyze the influence of the investment growth (capital), the average growth of the Â skilled-labor and unskilled-labor, the average educational attainment, as well as the government expenditure growth for education on the economic growth of the provinces in IndonesThe present study is descriptive as well as verificative by using pool least squares method. The data used is secondary such as panel data that consist of combination between time-series and cross-section from 26 provinces in Indonesia Â during period 1994â2008. The research findings indicate that (1) capital growth (investment-investment) is positively and significantly influence on the economic growth, (2) the growth of the skilled-labor is negatively and not significantly influence on the economic growth. (3) the growth of the unskilled-labor is positively and significantly influence on the economic growth (4) educational attainment average is positively and significantly influence on the economical growth and (5) the growth of the government expenditure for education is positively and significantly influence on the economic growth of the provinces in Indonesia.